Thermally conductive sheet, heat dissipation device, and method for manufacturing thermally conductive sheet
By using graphite particles (A) in the thermal conductivity, orientation of the thickness direction of the thermal layer, and forming a thermoplastic resin component and the adhesive layer of the thermal plastic resin on the main surface of the thermal conductivity, solve the problem of high thermal resistance of the existing heat conductive sheet, realize it, realize the realization of high heat resistance, realize the realization Lower thermal resistance and better thermal conductivity.
Patent Information
- Application Number
- CN202280095613.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-01-28
AI Technical Summary
When existing heat conductors face high heat generation caused by high performance and large-scale semiconductor packages, it is difficult to effectively reduce thermal resistance.
The thermal conductivity of the heating layer containing graphite particles (a) and resin components and the heating fillers is adopted. Graphite particles (A) are orientation in the thickness direction of the thermal conductivity. The adhesive layer is located on the main surface of the thermal conductivity, which contains the thermoplastic resin component and thermal filler.
The design of the orientation and adhesive layer of graphite particles (A) significantly reduces the thermal resistance of the thermal conductivity, and improves its thermal conductivity and dense.
Smart Images

Figure CN119384723A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat conducting sheet, a heat dissipation device and a method for manufacturing the heat conducting sheet. Background Art
[0002] In recent years, the increased density of wiring and electronic components in semiconductor packages using multilayer wiring boards has increased heat generation, and the increased heat generation per unit area due to the high integration of semiconductor elements has increased, and it is desired to improve the heat dissipation from the semiconductor package.
[0003] Generally, a heat sink is used that dissipates heat by sandwiching thermal grease or a thermally conductive sheet between a heat generating body such as a semiconductor package and a heat sink such as aluminum or copper and making them close together. Generally, a thermally conductive sheet is more convenient in terms of workability when assembling a heat sink than thermally conductive grease.
[0004] In recent years, CPU (Central Processing Unit) chips have tended to be larger in area due to multi-core and multi-chip development. In addition, there is a tendency for the crimping pressure between the heat-generating CPU and the heat sink to decrease. Therefore, the thermal conductive sheet is required to be flexible during crimping. In addition, the thermal conductive sheet is required to have excellent thermal conductivity with low thermal resistance even if the thermal conductive sheet becomes thicker due to the height difference of the chip.
[0005] As a thermally conductive sheet, a resin sheet filled with a thermally conductive filler is also known. As a resin sheet with excellent thermal conductivity filled with a thermally conductive filler, a resin sheet in which highly thermally conductive inorganic particles are selected as the thermally conductive filler and the inorganic particles are oriented perpendicularly to the sheet surface is proposed.
[0006] For example, there have been proposed thermally conductive sheets in which a thermally conductive filler (boron nitride) is oriented in a direction substantially perpendicular to the sheet surface (see, for example, Patent Document 1), and thermally conductive sheets in which carbon fibers dispersed in a gel-like substance are oriented perpendicularly to the sheet surface (see, for example, Patent Document 2).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2002-26202
[0010] Patent Document 2: Japanese Patent Application Publication No. 2001-250894 Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] Patent Documents 1 and 2 study methods for reducing thermal resistance by orienting thermally conductive fillers, carbon fibers, etc. in a direction perpendicular to the sheet surface. In order to cope with the increase in heat generation associated with the high performance and large-scale semiconductors, it is desirable to further reduce the thermal resistance of thermally conductive sheets. Therefore, it is preferred to achieve low thermal resistance based on considerations other than the orientation of thermally conductive fillers, carbon fibers, etc. contained in the thermally conductive sheet.
[0013] An object of one embodiment of the present invention is to provide a thermally conductive sheet having low thermal resistance, a heat sink including the thermally conductive sheet, and a method for manufacturing a thermally conductive sheet capable of manufacturing the thermally conductive sheet having low thermal resistance.
[0014] Means for solving technical problems
[0015] Specific means for solving the above technical problems include the following.
[0016] <1> A thermally conductive sheet comprising:
[0017] a heat conductive layer, the heat conductive layer comprising at least one graphite particle (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented in the thickness direction of the heat conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented in the thickness direction of the heat conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented in the thickness direction of the heat conductive layer; and
[0018] The adhesive layer comprises a resin component and a thermally conductive filler, and the adhesive layer is located on at least a portion of the main surface of the thermally conductive layer.
[0019] <2> The thermally conductive sheet according to <1>, wherein the resin component includes at least one selected from the group consisting of a curable resin component, a pressure-sensitive adhesive resin component, and a thermoplastic resin component.
[0020] <3> The thermally conductive sheet according to <2>, wherein the resin component is a curable resin component, and the adhesive layer is in a semi-cured state.
[0021] <4> The thermally conductive sheet according to any one of <1> to <3>, wherein the resin component includes a thermoplastic resin component.
[0022] <5> The thermally conductive sheet according to any one of <1> to <4>, wherein the thermoplastic resin component includes a thermoplastic epoxy resin.
[0023] <6> The thermally conductive sheet according to any one of <1> to <5>, wherein the thermally conductive filler is at least one particle selected from the group consisting of silver, copper, aluminum, aluminum oxide, aluminum hydroxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, silicon carbide, silicon dioxide, aluminum fluoride, calcium fluoride, and zinc oxide.
[0024] <7> The thermally conductive sheet according to <6>, wherein the thermally conductive filler is silver particles.
[0025] <8> The thermally conductive sheet according to any one of <1> to <7>, wherein the content of the thermally conductive filler is 70% by mass to 99% by mass based on the total amount of the adhesive layer.
[0026] <9> The thermally conductive sheet according to any one of <1> to <8>, wherein the adhesive layer has an average thickness of 2 μm to 50 μm.
[0027] <10> A heat dissipation device comprising a heat generating element, a heat dissipating element, and a thermally conductive sheet according to any one of <1> to <9> disposed between the heat generating element and the heat dissipating element,
[0028] The adhesive layer is located on at least a portion of at least one of the main surface of the heat conductive layer located on the heating element side and the main surface of the heat conductive layer located on the heat dissipating element side.
[0029] <11> A heat dissipation device comprising a heat generating element, a heat dissipating element, and a heat conductive sheet according to any one of <1> to <9> disposed between the heat generating element and the heat dissipating element,
[0030] In at least one of the interfaces between the heating element and the heat conductive sheet and between the heat dissipating element and the heat conductive sheet, the porosity calculated as the ratio of the area of the gas region to the area of the measurement region is 0% to 25%.
[0031] <11> A method for producing a thermally conductive sheet, the method comprising producing the thermally conductive sheet according to any one of <1> to <9>,
[0032] The method for producing the thermally conductive sheet comprises: preparing a composition containing the graphite particles (A); forming the thermally conductive layer using the composition; and forming an adhesive layer on at least a portion of a main surface of the thermally conductive layer.
[0033] Effects of the Invention
[0034] According to the present disclosure, it is possible to provide a thermally conductive sheet having low thermal resistance, a heat sink including the thermally conductive sheet, and a method for manufacturing a thermally conductive sheet capable of manufacturing the thermally conductive sheet having low thermal resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic structural diagram of a thermally conductive sheet according to one embodiment of the present invention.
[0036] Figure 2 This is a schematic cross-sectional view of a heat dissipation device in which a heat generating element is a semiconductor chip and a heat dissipating element is a heat sink according to an embodiment of the present invention.
[0037] Figure 3 This is a schematic structural diagram of a heat conductive sheet incorporated in a heat sink according to an embodiment of the present invention.
[0038] Figure 4 The diagrams show the states of interfaces obtained by image analysis in Examples 1 and 2 and Comparative Example 1.
[0039] Figure 5 The diagrams show the states of interfaces obtained by image analysis in Examples 3 to 7 and Comparative Examples 2 to 4. DETAILED DESCRIPTION
[0040] The following is a detailed description of the embodiments for implementing the present invention. However, the present invention is not limited to the following embodiments. In the following embodiments, unless otherwise specified, the constituent elements (including element steps, etc.) are not essential. The numerical values and their ranges are also the same and do not limit the present invention.
[0041] The term "process" used in the present disclosure includes not only a process that is independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.
[0042] In the present disclosure, in a numerical range expressed by “to”, the numerical values before and after “to” are included as the minimum value and the maximum value, respectively.
[0043] In the numerical range recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other segments. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.
[0044] In the present disclosure, each component may include a plurality of substances corresponding thereto. When a plurality of substances corresponding to each component are present in the composition, the content rate or content of each component refers to the total content rate or content of the plurality of substances present in the composition unless otherwise specified.
[0045] In the present disclosure, particles corresponding to each component may contain multiple types. When multiple types of particles corresponding to each component exist in the composition, the particle size of each component refers to the value of the mixture of the multiple types of particles present in the composition unless otherwise specified.
[0046] The term “layer” or “film” used in the present disclosure includes not only a case where the layer or film is formed throughout the entire region when the region where the layer or film exists is observed, but also a case where the layer or film is formed only in a part of the region.
[0047] The term "stacked" in the present disclosure means overlapping layers, and two or more layers may be combined together, or two or more layers may be detachable.
[0048] 〔Thermal Conductive Sheet〕
[0049] The thermally conductive sheet disclosed herein comprises: a thermally conductive layer, the thermally conductive layer containing at least one type of graphite particles (A) selected from flaky particles, ellipsoidal particles and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented along the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer; and an adhesive layer containing a resin component and a thermally conductive filler, wherein the adhesive layer is located on at least a portion of the main surface of the thermally conductive layer.
[0050] It is considered that the thermally conductive sheet of the present disclosure has excellent thermal conductivity in the thickness direction and exhibits low thermal resistance because it includes a thermally conductive layer in which the graphite particles (A) are oriented in the thickness direction of the thermally conductive layer.
[0051] It can be further considered that the thermally conductive sheet shows lower thermal resistance by having a thermally conductive layer containing graphite particles (A) and also having the above-mentioned adhesive layer. The reason is speculated as follows. It should be noted that the present disclosure is not limited by the following speculation. The thermally conductive sheet in which the graphite particles (A) are oriented in the thickness direction of the conductive layer has unevenness on the surface in contact with the adherend, and most of the thermal resistance comes from the resistance (also referred to as "contact thermal resistance") caused by the gap generated by the contact between the thermally conductive sheet and the adherends such as the heating element and the heat sink in contact with the thermally conductive sheet. The thermally conductive sheet disclosed in the present invention is provided with an adhesive layer containing a resin component and a thermally conductive filler on at least a portion of the main surface of the thermally conductive layer. When the thermally conductive sheet and the adherends such as the heating element and the heat sink are heated and pressed, the adhesive layer softens and deforms due to heat, pressure, etc. The gap generated when the thermally conductive sheet and the adherend are heated and pressed (for example, the gap caused by the unevenness of the thermally conductive sheet) is filled by the adhesive layer. As a result, the gap between the thermally conductive sheet and the adherend is reduced, and the thermally conductive sheet and the adherend are closely adhered to each other via the adhesive layer, so that the contact thermal resistance is greatly reduced.
[0052] Contact thermal resistance is also likely to occur when there are irregularities on the surface of the adherend, such as a heating element or a heat sink. In this case, it is difficult to reduce the thermal resistance by adjusting the orientation of the thermally conductive filler contained in the thermally conductive sheet. On the other hand, by using the thermally conductive sheet disclosed herein, the thermally conductive sheet and the adherend with irregularities on the surface can be closely attached with the aid of an adhesive layer. At this time, the gap generated when the thermally conductive sheet and the adherend are heated and pressed (for example, the gap caused by the irregularities of the adherend) is filled with the adhesive layer, so the contact thermal resistance is greatly reduced.
[0053] The thermally conductive layer included in the thermally conductive sheet of the present disclosure contains at least graphite particles (A), and may further contain components described below within a range that exhibits the effects of the present disclosure. Materials used in the thermally conductive layer of the present disclosure are described below.
[0054] <Graphite particles (A)>
[0055] The heat-conducting layer contained in the thermally conductive sheet contains graphite particles (A). It can be considered that the graphite particles (A) mainly play a role as a high thermal conductivity filler. The graphite particles (A) are at least one selected from flaky particles, ellipsoidal particles and rod-shaped particles. In addition, the graphite particles (A) are oriented in the thickness direction of the heat-conducting layer in the face direction in the case of flaky particles, oriented in the thickness direction of the heat-conducting layer in the case of ellipsoidal particles, and oriented in the thickness direction of the heat-conducting layer in the case of rod-shaped particles. In addition, it is preferred that the six-membered ring plane in the graphite particle (A) crystal is oriented in the face direction in the case of flaky particles, oriented in the long axis direction in the case of ellipsoidal particles, and oriented in the long axis direction in the case of rod-shaped particles. The six-membered ring plane refers to the face of the six-membered ring formed in the hexagonal crystal system, that is, the (0001) crystal plane.
[0056] The shape of the graphite particles (A) is more preferably flaky. The selection of flaky graphite particles tends to further improve thermal conductivity. This is believed to be because, for example, flaky graphite particles are more easily oriented in a predetermined direction in the thermal conductive layer.
[0057] Whether the six-membered ring planes in the crystal of the graphite particle (A) are oriented along the plane direction of the flaky particles, the long axis direction of the ellipsoidal particles, or the long axis direction of the rod-shaped particles can be confirmed by X-ray diffraction measurement. Specifically, the orientation direction of the six-membered ring planes in the crystal of the graphite particle (A) is confirmed by the following method.
[0058] First, a sample sheet for measurement is prepared in which the plane direction of the flaky particles of the graphite particles (A), the major axis direction of the ellipsoidal particles, or the major axis direction of the rod-shaped particles are oriented along the plane direction of the sheet. Specific methods for preparing the sample sheet for measurement include, for example, the following methods.
[0059] A mixture of a resin and graphite particles (A) in an amount of 10% by volume or more relative to the resin is formed into a sheet. The "resin" used is not particularly limited as long as it does not show a peak that hinders X-ray diffraction and can be formed into a sheet. Specifically, an amorphous resin having cohesive force as a binder such as acrylic rubber, NBR (acrylonitrile butadiene rubber), and SIBS (styrene-isobutylene-styrene copolymer) can be used.
[0060] The sheet of the mixture is pressed to less than 1 / 10 of the original thickness, and a plurality of the pressed sheets are stacked to form a laminate. The operation of further pressing the laminate to less than 1 / 10 is repeated more than 3 times to obtain a sample sheet for measurement. By this operation, in the sample sheet for measurement, the graphite particles (A) are oriented in the plane direction along the plane direction of the sample sheet for measurement in the case of flaky particles, in the case of ellipsoidal particles, in the state of being oriented in the plane direction of the sample sheet for measurement, and in the case of rod-shaped particles, in the state of being oriented in the plane direction of the sample sheet for measurement.
[0061] The surface of the sample sheet for measurement prepared as described above was subjected to X-ray diffraction measurement. The height H1 of the peak corresponding to the (110) plane of graphite appearing near 2θ = 77° and the height H2 of the peak corresponding to the (002) plane of graphite appearing near 2θ = 27° were measured. The value obtained by dividing H1 by H2 of the sample sheet for measurement prepared in this way was 0 to 0.02.
[0062] Therefore, "the hexagonal ring planes in the crystals of the graphite particles (A) are oriented in the plane direction in the case of flaky particles, in the major axis direction in the case of ellipsoidal particles, and in the major axis direction in the case of rod-shaped particles" means that the surface of a sheet containing graphite particles (A) is measured by X-ray diffraction, and the value obtained by dividing the height of the peak corresponding to the (110) plane of the graphite particles (A) appearing near 2θ=77° by the height of the peak corresponding to the (002) plane of the graphite particles (A) appearing near 2θ=27° is 0 to 0.02.
[0063] In the present disclosure, X-ray diffraction measurement is performed under the following conditions.
[0064] Device: For example, Burker AXS Corporation "D8DISCOVER"
[0065] X-ray source: CuKα with a wavelength of 1.5406nm, 40kV, 40mA
[0066] Step length (measurement of stride width): 0.01°
[0067] Step time: 720 seconds
[0068] Here, “the graphite particles are oriented in the thickness direction of the heat conductive layer in the case of flaky particles, in the thickness direction of the heat conductive layer in the case of ellipsoidal particles, and in the thickness direction of the heat conductive layer in the case of rod-shaped particles” means that in the case of flaky particles, the angle formed by the surface direction and the surface (main surface) of the heat conductive layer (hereinafter also referred to as “orientation angle”) is 60° or more, in the case of ellipsoidal particles, the angle formed by the long axis direction and the surface (main surface) of the heat conductive layer (hereinafter also referred to as “orientation angle”) is 60° or more, and in the case of rod-shaped particles, the angle formed by the long axis direction and the surface (main surface) of the heat conductive layer (hereinafter also referred to as “orientation angle”) is 60° or more. The orientation angle is preferably 80° or more, more preferably 85° or more, and even more preferably 88° or more.
[0069] The orientation angle is an average value obtained by observing a cross section of the heat conductive layer with a SEM (scanning electron microscope) and measuring the angles (orientation angles) formed by the plane direction in the case of flaky particles, the major axis direction in the case of ellipsoidal particles, and the major axis direction in the case of rod-shaped particles and the surface (main surface) of the heat conductive layer for 50 arbitrary graphite particles (A).
[0070] The particle size of the graphite particles (A) is not particularly limited. The average particle size of the graphite particles (A) is preferably more than 1 / 2 of the average thickness of the heat-conducting layer and less than the average thickness in terms of the mass average particle size. If the mass average particle size of the graphite particles (A) is more than 1 / 2 of the average thickness of the heat-conducting layer, an effective heat conduction path can be formed in the heat-conducting layer, and there is a tendency for the thermal conductivity to be improved. If the mass average particle size of the graphite particles (A) is less than the average thickness of the heat-conducting layer, it is possible to suppress the graphite particles (A) from protruding from the surface of the heat-conducting layer, and there is a tendency for the surface of the heat-conducting layer to have excellent adhesion.
[0071] There is no particular limitation on the method for preparing the thermally conductive layer in a manner that the plane direction in the case of flaky particles, the major axis in the case of ellipsoidal particles, and the major axis direction in the case of rod-shaped particles are oriented in the thickness direction, and for example, the method described in Japanese Patent Publication No. 2008-280496 can be used. Specifically, the following method can be used: a sheet is prepared using a composition, the sheets are stacked to prepare a laminate, and the side end surface of the laminate (for example, at an angle of 0° to 30° relative to the normal line from the main surface of the laminate) is sliced (hereinafter also referred to as "laminate slicing method").
[0072] In addition, when the above-mentioned stacking and slicing method is used, the particle size of the graphite particles (A) used as the raw material is preferably 1 / 2 times or more of the average thickness of the thermal conductive layer in terms of mass average particle size, and may also exceed the average thickness. The reason why the particle size of the graphite particles (A) used as the raw material may also exceed the average thickness of the thermal conductive layer is that, for example, even if graphite particles (A) having a particle size exceeding the average thickness of the thermal conductive layer are contained, since the thermal conductive layer is formed by slicing together with the graphite particles (A), the graphite particles (A) will not protrude from the surface of the thermal conductive layer. In addition, when slicing together with the graphite particles (A), a large number of graphite particles (A) that penetrate the thickness direction of the thermal conductive layer are generated, which can form an extremely effective thermal conductive path, and there is a tendency for the thermal conductivity to be further improved.
[0073] When the stacking section method is used, the particle size of the graphite particles (A) used as the raw material is more preferably 1 to 5 times the average thickness of the heat-conducting layer in terms of mass average particle size, and more preferably 2 to 4 times. If the mass average particle size of the graphite particles (A) is more than 1 times the average thickness of the heat-conducting layer, an effective heat-conducting path can be further formed, and the thermal conductivity is further improved. If it is less than 5 times the average thickness of the heat-conducting layer, the area occupied by the graphite particles (A) on the surface portion can be suppressed from becoming too large, and the reduction of adhesion can be suppressed.
[0074] The mass average particle size (D50) of the graphite particles (A) is measured using a laser diffraction particle size distribution device (e.g., Microtrac Series MT3300, manufactured by Nikkiso Co., Ltd.) using a laser diffraction / scattering method, and corresponds to a particle size at which the mass accumulation reaches 50% when a mass cumulative particle size distribution curve is plotted from the smaller particle size side.
[0075] The heat conductive layer may contain graphite particles other than flaky particles, ellipsoidal particles and rod-shaped particles, and may contain spherical graphite particles, artificial graphite particles, exfoliated graphite particles, acid-treated graphite particles, expanded graphite particles, carbon fiber flakes and the like.
[0076] The graphite particles (A) are preferably flaky particles, and flaky expanded graphite particles obtained by pulverizing flaky expanded graphite are preferred because flaky particles having high crystallinity and large particle size can be easily obtained.
[0077] For example, from the viewpoint of the balance between thermal conductivity and adhesion, the content of the graphite particles (A) in the thermal conductive layer is preferably 15 to 50% by volume, more preferably 20 to 45% by volume, and even more preferably 25 to 40% by volume.
[0078] When the content of the graphite particles (A) is 15% by volume or more, thermal conductivity tends to be improved, while when the content of the graphite particles (A) is 50% by volume or less, reduction in pressure-sensitive adhesiveness and adhesion tends to be suppressed.
[0079] Furthermore, when the heat conductive layer contains graphite particles other than flaky particles, ellipsoidal particles, and rod-shaped particles, the content of the entire graphite particles is preferably within the above range.
[0080] The content (volume %) of the graphite particles (A) is a value obtained by the following formula.
[0081] Content of graphite particles (A) (volume %) = [(Aw / Ad) / {(Aw / Ad)+(Xw / Xd)}]×100
[0082] Aw: mass composition of graphite particles (A) (mass %)
[0083] Xw: Mass composition of other optional components (mass %)
[0084] Ad: Density of graphite particles (A) (Calculated with Ad being 2.1 in this disclosure)
[0085] Xd: Density of any other component
[0086] <Ingredient (B) that is liquid at 25°C>
[0087] The heat conductive layer contained in the heat conductive sheet of the present disclosure may also contain a component that is liquid at 25°C (hereinafter also referred to as "liquid component (B)"). In the present disclosure, "liquid at 25°C" means a substance that exhibits fluidity and viscosity at 25°C, and the viscosity, which is a measure of viscosity, is 0.0001 Pa·s to 1000 Pa·s at 25°C. "Viscosity" in the present disclosure is defined as the viscosity of a liquid at 25°C using a rheometer at 5.0s -1 Specifically, the "viscosity" is the shear viscosity measured at a temperature of 25°C using a rotational shear viscometer equipped with a cone plate (diameter 40 mm, cone angle 0°).
[0088] The viscosity of the liquid component (B) at 25°C is preferably 0.001 Pa·s to 100 Pa·s, more preferably 0.01 Pa·s to 10 Pa·s.
[0089] The liquid component (B) is not particularly limited as long as it is liquid at 25°C, and is preferably a high molecular compound (polymer). Examples of the liquid component (B) include polybutene, polyisoprene, polysulfide, acrylonitrile rubber, silicone rubber, hydrocarbon resin, terpene resin, acrylic resin, etc. Among them, from the viewpoint of heat resistance, the liquid component (B) preferably contains polybutene. The liquid component (B) may be used alone or in combination of two or more.
[0090] Among them, polybutene refers to a polymer obtained by polymerizing isobutylene or normal butene. It also includes a polymer obtained by copolymerizing isobutylene and normal butene. Structurally, it refers to a polymer having a structural unit represented by "-CH2-C(CH3)2-" or "-CH2-CH(CH2CH3)-". It is sometimes also called polyisobutylene. As long as polybutene contains the above structure, there is no particular limitation on other structures.
[0091] Examples of polybutene include homopolymers of butene and copolymers of butene and other monomer components. Examples of copolymers with other monomer components include copolymers of isobutylene and styrene or copolymers of isobutylene and ethylene. The copolymer may be any of a random copolymer, a block copolymer, and a graft copolymer.
[0092] Examples of polybutene include "NOF Polybutene" produced by NOF Corporation. TM EMAWET (registered trademark)”, “Nisseki Polybutene” of JXTG Nippon Oil & Energy Corporation, “Tetrax” of JXTG Nippon Oil & Energy Corporation, “Himol” of JXTG Nippon Oil & Energy Corporation, and “Polyisobutylene” of Tomoe Industries Co., Ltd.
[0093] It is believed that the liquid component (B) mainly functions as a stress relaxant and a pressure-sensitive adhesive agent having excellent heat resistance and humidity resistance. In addition, the cohesive force and fluidity during heating tend to be further improved by using the hot melt agent (D) described below.
[0094] From the viewpoint of further improving pressure-sensitive adhesive force, adhesion, sheet strength, hydrolysis resistance, etc., the content of the liquid component (B) in the thermally conductive layer is preferably 10% to 55% by volume, more preferably 15% to 50% by volume, and even more preferably 20% to 50% by volume.
[0095] When the content of the liquid component (B) is 10% by volume or more, the pressure-sensitive adhesiveness and adhesion tend to be further improved. When the content of the liquid component (B) is 55% by volume or less, the decrease in sheet strength and thermal conductivity tends to be more effectively suppressed.
[0096] <Acrylate polymer (C)>
[0097] The heat conductive layer included in the heat conductive sheet may further contain an acrylate polymer (C). It is considered that the acrylate polymer (C) mainly functions as a pressure-sensitive adhesive agent and an elasticity-imparting agent for restoring the thickness to follow the warping.
[0098] As the acrylic ester polymer (C), for example, it is preferred to use an acrylic ester polymer (so-called acrylic rubber) obtained by copolymerizing butyl acrylate, ethyl acrylate, acrylonitrile, acrylic acid, glycidyl methacrylate, 2-vinylhexyl acrylate, etc. as main raw material components and methyl acrylate, etc. as needed. The acrylic ester polymer (C) may be used alone or in combination of two or more.
[0099] The weight average molecular weight of the acrylic polymer (C) is preferably 100,000 to 1,000,000, more preferably 250,000 to 700,000, and even more preferably 400,000 to 600,000. A weight average molecular weight of 100,000 or more tends to provide excellent film strength, while a weight average molecular weight of 1,000,000 or less tends to provide excellent flexibility.
[0100] The weight average molecular weight is determined by gel permeation chromatography using a calibration curve of standard polystyrene.
[0101] The glass transition temperature (Tg) of the acrylic polymer (C) is preferably 20° C. or lower, more preferably -70° C. to 0° C., and further preferably -50° C. to -20° C. When the glass transition temperature is 20° C. or lower, the acrylate polymer (C) tends to have excellent flexibility and pressure-sensitive adhesiveness.
[0102] The glass transition temperature (Tg) can be calculated by performing dynamic viscoelasticity measurement by stretching and tan δ derived from the measurement.
[0103] The acrylate polymer (C) may be present in the entire thermal conductive layer by internal addition, or may be locally present on the surface by surface coating or impregnation. In particular, coating or impregnation on one side is preferred because strong adhesion can be imparted only to one side, which is preferred from the perspective of obtaining a sheet with good workability.
[0104] The content of the acrylic ester polymer (C) in the heat conductive layer is preferably 3% to 25% by volume, more preferably 5% to 20% by volume, and even more preferably 7% to 15% by volume.
[0105] <Hot melt (D)>
[0106] The heat conductive layer included in the heat conductive sheet may further contain a hot melt (D). The hot melt (D) has the effect of increasing the strength of the heat conductive layer and improving the fluidity when heated.
[0107] Examples of the hot melt agent (D) include aromatic petroleum resins, terpene phenolic resins, and cyclopentadiene petroleum resins. In addition, the hot melt agent (D) may be a hydrogenated aromatic petroleum resin or a hydrogenated terpene phenolic resin. The hot melt agent (D) may be used alone or in combination of two or more.
[0108] Among them, when polybutene is used as the liquid component (B), the hot melt (D) preferably contains at least one selected from hydrogenated aromatic petroleum resins and hydrogenated terpene phenolic resins. These hot melts (D) have high stability and excellent compatibility with polybutene, and therefore, when constituting the heat conductive layer, there is a tendency to achieve better thermal conductivity, flexibility, and workability.
[0109] Examples of commercially available hydrogenated aromatic petroleum resins include "Arkon" from Arakawa Chemical Industries, Ltd. and "i-marv" from Idemitsu Kosan Co., Ltd. In addition, examples of commercially available hydrogenated terpene phenolic resins include "CLEARON" from Yasuhara Chemical Co., Ltd. In addition, examples of commercially available cyclopentadiene petroleum resins include "Quintone" from Japan Zeon Corporation and "MARUKA LYNCUR" from Maruzen Petrochemical Co., Ltd.
[0110] The hot melt (D) is solid at 25°C, and preferably has a softening temperature of 40°C to 150°C. If a thermoplastic resin is used as the hot melt (D), the softening fluidity during thermocompression bonding is improved, resulting in a tendency to improve adhesion. In addition, if the softening temperature is above 40°C, the cohesive force near room temperature can be maintained, resulting in a tendency to easily obtain the required sheet strength and excellent handling properties. If the softening temperature is below 150°C, the softening fluidity during thermocompression bonding becomes high, resulting in a tendency to improve adhesion. The softening temperature is more preferably 60°C to 120°C. In addition, the softening temperature is measured by the ring and ball method (JIS K2207: 1996).
[0111] From the viewpoint of improving pressure-sensitive adhesive force, adhesion, sheet strength, etc., the content of the hot melt agent (D) in the heat conductive layer is preferably 3 to 25 volume %, more preferably 5 to 20 volume %, and further preferably 5 to 15 volume %.
[0112] When the content of the hot melt agent (D) is 3% by volume or more, pressure-sensitive adhesive strength, heating fluidity, sheet strength, etc. tend to be sufficient, and when it is 25% by volume or less, flexibility tends to be sufficient, resulting in excellent handleability and heat cycle resistance.
[0113] <Antioxidant (E)>
[0114] The heat-conducting layer contained in the thermally conductive sheet may also contain an antioxidant (E) for the purpose of imparting thermal stability at high temperatures. As the antioxidant (E), phenolic antioxidants, phosphorus antioxidants, amine antioxidants, sulfur antioxidants, hydrazine antioxidants, amide antioxidants, etc. may be cited. The antioxidant (E) may be appropriately selected according to the temperature conditions used, and is more preferably a phenolic antioxidant. One antioxidant (E) may be used alone, or two or more may be used in combination.
[0115] Examples of commercially available phenolic antioxidants include ADK STAB AO-50, ADK STAB AO-60, and ADK STAB AO-80 from ADEKA Corporation.
[0116] The content of the antioxidant (E) in the thermal conductive layer is not particularly limited, but is preferably 0.1% to 5% by volume, more preferably 0.2% to 3% by volume, and further preferably 0.3% to 1% by volume. If the content of the antioxidant (E) is 0.1% by volume or more, a sufficient antioxidant effect tends to be obtained. If the content of the antioxidant (E) is 5% by volume or less, a decrease in the strength of the thermal conductive layer tends to be suppressed.
[0117] <Other ingredients>
[0118] According to the purpose, the heat-conducting layer contained in the thermally conductive sheet may also contain other components except graphite particles (A), liquid components (B), acrylate polymers (C), hot melts (D), and antioxidants (E). For example, from the viewpoint of flame retardancy, the heat-conducting layer may also contain a flame retardant. The flame retardant is not particularly limited and can be appropriately selected from commonly used flame retardants. For example, red phosphorus flame retardants and phosphate flame retardants can be listed. Among them, from the viewpoint of excellent safety and improving adhesion through plasticizing effect, phosphate flame retardants are preferred.
[0119] As the red phosphorus flame retardant, in addition to using simple red phosphorus particles, various coated red phosphorus flame retardants, masterbatch red phosphorus flame retardants, etc. can also be used for the purpose of improving safety or stability. Specifically, Nobaredo, Nobaclexel, Nobacle, Nobaperet (all trade names) of Phosphorus Chemical Industry Co., Ltd. can be cited.
[0120] As phosphate flame retardants, there can be listed aliphatic phosphates such as trimethyl phosphate, triethyl phosphate, and tributyl phosphate; aromatic phosphates such as triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, cresyl di(2,6-xylyl) phosphate, tri(tert-butylphenyl) phosphate, tri(isopropylated phenyl) phosphate, and triaryl phosphate isopropylate; aromatic condensed phosphates such as resorcinol bisdiphenyl phosphate, bisphenol A bis(diphenyl phosphate), and resorcinol bis[di(dimethylphenyl) phosphate], etc.
[0121] Among them, bisphenol A bis(diphenyl phosphate) is preferred from the viewpoint of being excellent in hydrolysis resistance and having an excellent effect of improving adhesion due to a plasticizing effect.
[0122] The content of the flame retardant in the thermal conductive layer is not particularly limited and can be used in an amount that can exert flame retardancy, but is preferably set to about 30 volume % or less. From the viewpoint of suppressing the deterioration of thermal resistance caused by the leakage of the flame retardant component to the surface of the thermal conductive layer, it is preferably set to 20 volume % or less.
[0123] The average thickness of the heat-conducting layer is not particularly limited and can be appropriately selected according to the purpose. The thickness of the heat-conducting layer can be appropriately selected according to the specifications of the semiconductor package used. The smaller the thickness, the lower the thermal resistance tends to be, and the larger the thickness, the better the warpage tracking property tends to be. The average thickness of the heat-conducting layer can be 20 μm to 3000 μm, preferably 30 μm to 500 μm, and more preferably 50 to 400 μm from the viewpoint of thermal conductivity and adhesion.
[0124] The cross section of the object to be measured is observed using an electron microscope or the thickness of three locations is randomly measured using a micrometer, and the arithmetic mean value is calculated as the average thickness of the heat conductive layer.
[0125] <Adhesive layer>
[0126] The thermally conductive sheet of the present disclosure includes an adhesive layer including a resin component and a thermally conductive filler, and the adhesive layer is located on at least a portion of the main surface of the thermally conductive layer.
[0127] As the resin component, there can be listed curable resin components, pressure-sensitive adhesive resin components, thermoplastic resin components, etc. As the curable resin component, there can be listed thermosetting resin components, photocurable resin components, etc. The resin component can contain more than one curable resin component, can also contain more than one pressure-sensitive adhesive resin component, and can also contain more than one thermoplastic resin component. In addition, the resin component can also be a mixture of more than two resin components.
[0128] As the curable resin component, for example, epoxy resin, phenolic resin, melamine resin, urea resin, unsaturated polyester resin, alkyd resin, urethane resin, polyimide resin such as bismaleimide resin, polyamide resin, polyamideimide resin, silicone resin and thermosetting (meth) acrylic resin can be listed. Among them, epoxy resin is preferred from the viewpoint of adhesion.
[0129] As pressure-sensitive adhesive resin components, thermoplastic resin components, etc., for example, polyethylene (PE), polypropylene (PP), polycarbonate (PC), polystyrene, polyvinyl chloride, vinyl polymers, polyesters, polyamides, acrylonitrile-butadiene-styrene copolymer resins (ABS resins), thermoplastic (meth) acrylic resins, acrylonitrile-ethylene-propylene-diene-styrene copolymer resins (AES resins), thermoplastic epoxy resins, phenoxy resins, and thermoplastic elastomers can be cited. By using thermoplastic resin components, it is easy to soften and melt the adhesive layer by heating, and the recyclability and repairability are excellent. Furthermore, compared with the thermal conductive sheet using a curable resin component (especially a thermosetting resin component), the thermal conductive sheet using a thermoplastic resin component has better storage stability and can be stored at room temperature. Among them, from the viewpoint that the viscosity can be reduced by heating and the gap between the adherend and the thermal conductive sheet can be further reduced, the thermoplastic resin component is preferably a thermoplastic epoxy resin.
[0130] The thermoplastic resin component may be an amorphous thermoplastic resin, and the amorphous thermoplastic resin may be, for example, at least one of a thermoplastic epoxy resin and a phenoxy resin. An amorphous thermoplastic resin refers to a resin having a melting point (Tm), but in a measurement using a differential scanning calorimeter (DSC), an endothermic peak accompanying melting cannot be confirmed as a clear endothermic peak, or the endothermic peak is very small.
[0131] The heat of fusion of the amorphous thermoplastic resin is preferably 15 J / g or less, more preferably 11 J / g or less, further preferably 7 J / g or less, particularly preferably 4 J / g or less, and most preferably the melting peak is below the detection limit.
[0132] The heat of fusion is calculated from the area of the endothermic peak of DSC (differential scanning calorimeter) and the mass of the thermoplastic resin component. In this case, the heat of fusion is calculated using the mass of the thermoplastic resin component excluding the components contained in the adhesive layer such as the thermally conductive filler.
[0133] For example, the heat of fusion can be determined as follows.
[0134] First, 2 mg to 10 mg of a sample is weighed and placed in an aluminum pan, and the temperature is raised to 200°C or higher at 10°C / min using a DSC (e.g., DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. Next, the heat of fusion is calculated from the area of the endothermic peak during melting obtained from the DSC curve and the weighed value.
[0135] The thermoplastic epoxy resin is preferably a polymer of (a) a bifunctional epoxy resin monomer or oligomer and (b) a bifunctional compound containing two identical or different functional groups selected from phenolic hydroxyl, carboxyl, mercapto, isocyanate and cyanate groups. The aforementioned polymer can be produced by heating the components (a) and (b) in the presence of a catalyst such as an imidazole catalyst.
[0136] The (a) bifunctional epoxy resin monomer or oligomer refers to an epoxy resin monomer or oligomer having two epoxy groups in the molecule.
[0137] Specific examples of the above (a) include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bifunctional phenol novolac type epoxy resins, bisphenol AD type epoxy resins, biphenyl type epoxy resins, bifunctional naphthalene type epoxy resins, bifunctional alicyclic epoxy resins, bifunctional glycidyl ester type epoxy resins (e.g., diglycidyl phthalate, diglycidyl tetrahydrophthalate, and diglycidyl dimer acid ester), bifunctional glycidyl amine type epoxy resins (e.g., diglycidyl aniline and diglycidyl toluidine), bifunctional heterocyclic epoxy resins, bifunctional diaryl sulfone type epoxy resins, hydroquinone type epoxy resins (e.g., hydroquinone diglycidyl ether, 2,5-di-tert-butylphenylene glycol), and diglycidyl ether. diphenol diglycidyl ether and resorcinol diglycidyl ether), bifunctional alkylene glycidyl ether compounds (such as butanediol diglycidyl ether, butene diol diglycidyl ether and butynediol diglycidyl ether), bifunctional glycidyl group-containing hydantoin compounds (such as 1,3-diglycidyl-5,5-dialkylhydantoin and 1-glycidyl-3-(glycidyloxyalkyl)-5,5-dialkylhydantoin), bifunctional glycidyl group-containing siloxane (such as 1,3-bis(3-glycidyloxypropyl)-1,1,3,3-tetramethyldisiloxane and α,β-bis(3-glycidyloxypropyl)polydimethylsiloxane) and their modified products. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin and biphenyl type epoxy resin are preferred from the viewpoint of reactivity and workability.
[0138] Examples of the bifunctional compound containing a phenolic hydroxyl group of (b) include mononuclear aromatic dihydroxy compounds having one benzene ring, such as catechol, resorcinol, and hydroquinone; bisphenols such as bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)methane (bisphenol F), bis(4-hydroxyphenyl)ethane (bisphenol AD), and bis(4-hydroxyphenyl)sulfone (bisphenol S); compounds having a condensed ring, such as dihydroxynaphthalene; bifunctional phenol compounds having an allyl group introduced, such as diallylresorcinol, diallylbisphenol A, and triallyldihydroxybiphenyl, and dibutylbisphenol A.
[0139] Examples of the bifunctional compound containing a carboxyl group (b) include adipic acid, succinic acid, malonic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, and terephthalic acid.
[0140] Examples of the bifunctional compound containing a mercapto group (b) include ethylene glycol bisthioglycolate and ethylene glycol bisthiopropionate.
[0141] Examples of the bifunctional compound containing an isocyanate group (b) include diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMDI), and toluene diisocyanate (TDI).
[0142] Examples of the bifunctional compound containing a cyanate group (b) include 2,2-bis(4-cyanatophenyl)propane, 1,1-bis(4-cyanatophenyl)ethane, and bis(4-cyanatophenyl)methane.
[0143] Among the above (b), a bifunctional compound containing a phenolic hydroxyl group is preferred from the viewpoint of obtaining a thermoplastic polymer, a bifunctional compound containing two phenolic hydroxyl groups and a bisphenol structure or a biphenyl structure is preferred from the viewpoint of heat resistance and adhesion, and bisphenol A, bisphenol F or bisphenol S is preferred from the viewpoint of heat resistance and cost.
[0144] When the above-mentioned (a) is a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a bisphenol S type epoxy resin, or a biphenyl type epoxy resin, and the above-mentioned (b) is bisphenol A, bisphenol F, or bisphenol S, the polymer obtained by the polymerization of the above-mentioned (a) and (b) preferably has a main skeleton composed of a p-phenylene structure and an ether bond, a main chain in which these are connected by an alkylene group, and a structure in which a hydroxyl group generated by addition polymerization is arranged on the side chain.
[0145] The linear structure composed of the p-phenylene skeleton can improve the mechanical strength of the polymer after polymerization, and the hydroxyl groups arranged in the side chains can improve the adhesion. As a result, high adhesive strength can be achieved while maintaining the workability of the thermosetting resin.
[0146] The epoxy equivalent (molecular weight / number of epoxy groups) of the thermoplastic epoxy resin may be 1600 g / eq or more, 2000 g / eq or more, 5000 g / eq or more, or 9000 g / eq or more.
[0147] The epoxy equivalent of the epoxy resin adopts a value measured by a method based on JIS K 7236:2009.
[0148] The adhesive layer may contain a phenoxy resin as a thermoplastic resin component.
[0149] Phenoxy resin is a polyhydroxy polyether synthesized from bisphenols and epichlorohydrin, and has thermoplastic properties.
[0150] In the manufacture of phenoxy resin, there are known methods of utilizing the direct reaction of dihydric phenols with epichlorohydrin, and methods of utilizing the addition polymerization of diglycidyl ethers of dihydric phenols with diols. In the case of the direct reaction of dihydric phenols with epichlorohydrin, as dihydric phenols, for example, phenols such as bisphenol A, bisphenol F, bisphenol S, biphenol, biphenyl glycol, diphenylfluorene, and aliphatic diols such as ethylene glycol, propylene glycol, and diethylene glycol can be listed. Among them, from the viewpoints of cost, adhesion, viscosity, heat resistance, etc., bisphenol A, bisphenol F, bisphenol S, etc. are preferred. They can be used alone or in combination of two or more.
[0151] The phenoxy resin preferably has a chemical structure similar to that of the epoxy resin, and has a p-phenylene structure and an ether bond as the main skeleton, and has a structure in which hydroxyl groups are arranged in the main chain and side chains formed by connecting these.
[0152] For thermoplastic epoxy resins and phenoxy resins, the polystyrene-converted values measured by GPC (gel permeation chromatography), i.e., weight average molecular weights, are each independently preferably 10,000 to 500,000, more preferably 18,000 to 300,000, and further preferably 20,000 to 200,000. The weight average molecular weight is a value of molecular weight calculated based on the elution peak position detected by GPC and converted to standard polystyrene. If the weight average molecular weight is within the range of this value, the balance between thermoplasticity and heat resistance is good. If the weight average molecular weight is 10,000 or more, the heat resistance is excellent, and if it is 500,000 or less, the viscosity during melting becomes low and the adhesion becomes high.
[0153] Examples of thermally conductive fillers include metal-containing particles and non-metallic particles having excellent thermal conductivity, such as metals, metal oxides, metal nitrides, metal hydroxides, metal carbides, metal fluorides, and carbon. The thermally conductive filler may be a filler having a thermal conductivity of 10 W / (m·K) or more. The thermally conductive filler may be insulating or conductive.
[0154] The thermally conductive filler may be at least one particle selected from the group consisting of silver, copper, aluminum, aluminum oxide, aluminum hydroxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, silicon carbide, silicon dioxide, aluminum fluoride, calcium fluoride, and zinc oxide. Among them, silver particles are preferred from the viewpoint of thermal conductivity.
[0155] Boron nitride is an insulating particle, and from this aspect, it is preferably used in applications requiring insulation. However, boron nitride is flaky in shape, has anisotropic thermal conductivity, and is easily oriented in the plane direction, resulting in a tendency for the thermal conductivity in the thickness direction to decrease. Therefore, when using boron nitride, from the viewpoint of thermal conductivity, it is necessary to form an adhesive layer in a manner such that the boron nitride is oriented in the thickness direction, and the formation process of the adhesive layer tends to become complicated.
[0156] On the other hand, compared with ceramic fillers such as boron nitride, metal particles such as silver, copper, and aluminum have high thermal conductivity and small anisotropy of thermal conductivity. Therefore, when forming an adhesive layer, it is not necessary to orient the metal particles in the thickness direction, and it is easy to form an adhesive layer with excellent thermal conductivity, and the thermal resistance of the thermal conductive sheet can be appropriately reduced. Therefore, by using silver particles as metal particles, sintering between particles can be performed at a lower temperature. Therefore, a network of silver particles can be formed by sintering, and there is a tendency to obtain a higher thermal conductivity than other thermally conductive fillers. In addition, the sintered silver particles have excellent adhesion to adherends such as heating elements and heat sinks, so there is a tendency that thermal resistance can be further reduced.
[0157] The thermally conductive filler preferably contains silver particles. When the thermally conductive filler contains silver particles, the content of the silver particles may be 50 to 100 mass %, 80 to 100 mass %, or 90 to 100 mass % relative to 100 mass % of the thermally conductive filler.
[0158] From the viewpoint of excellent thermal conductivity and further reducing the gap between the adherend and the thermally conductive sheet, the particle size of the thermally conductive filler may be 0.1 μm to 50 μm, 0.2 μm to 20 μm, or 0.5 μm to 10 μm.
[0159] The particle size (D50) of the thermally conductive filler is measured using a laser diffraction particle size distribution device (e.g., "Microtrac Series MT3300" manufactured by Nikkiso Co., Ltd.) using a laser diffraction / scattering method, and corresponds to the particle size at which the mass accumulation reaches 50% when a mass cumulative particle size distribution curve is plotted from the smaller particle size side.
[0160] In the thermally conductive sheet disclosed herein, the adhesive layer may be located on at least a portion of the main surface of the thermally conductive layer. The adhesive layer may be located on the entire main surface, or on a portion of the main surface (e.g., a portion in contact with an adherend such as a heating element or a heat sink).
[0161] The adhesive layer may be located on one main surface or on both main surfaces.
[0162] For example, from the viewpoint of the balance between thermal conductivity and adhesion, the content of the resin component in the adhesive layer is preferably 1 to 30% by mass, more preferably 3 to 25% by mass, and even more preferably 5 to 20% by mass relative to the total amount of the adhesive layer.
[0163] When the adhesive layer contains a thermoplastic resin component, the content of the thermoplastic resin component may be 50% by mass or more, 60% by mass or more, 80% by mass or more, or 90% by mass or more relative to the total amount of the resin component.
[0164] The upper limit of the content of the thermoplastic resin component is not particularly limited, and may be 100% by mass or 95% by mass or less.
[0165] For example, from the viewpoint of the balance between thermal conductivity and adhesion, the content of the thermally conductive filler in the adhesive layer is preferably 70% to 99% by mass, more preferably 75% to 97% by mass, and even more preferably 80% to 95% by mass relative to the total amount of the adhesive layer.
[0166] The total content of the resin component and the thermally conductive filler contained in the adhesive layer may be 80% by mass to 100% by mass, or 90% by mass to 100% by mass, based on the total amount of the adhesive layer.
[0167] The adhesive layer may or may not contain components other than the resin component and the thermally conductive filler. Components other than the resin component and the thermally conductive filler include the hot melt agent (D), antioxidant (E), and other components described in the thermally conductive layer.
[0168] When the adhesive layer contains a thermosetting resin component, the adhesive layer is preferably in a semi-cured state from the viewpoint of improving workability. For example, the semi-cured adhesive layer is obtained by heating, drying, etc. a resin composition containing a thermosetting resin component and a thermally conductive filler.
[0169] In the present disclosure, the semi-cured state refers to the state in which the viscosity of the adhesive layer is 10 4 Pa·s~10 6 Pa·s. The above viscosity was measured by DMA (dynamic viscoelasticity measuring device; frequency 1 Hz, load 10 g; heating rate 20° C. / min).
[0170] The method for obtaining the semi-cured adhesive layer is not particularly limited. For example, a resin composition containing a thermosetting resin component, a thermally conductive filler, a solvent, etc. is applied to the main surface of the thermally conductive layer, and the applied resin composition is heated, dried, etc. Alternatively, the resin composition may be applied to the release film, and then, after heating, drying, etc., the adhesive layer formed by the heated, dried, etc. resin composition is hot-roll laminated to the main surface of the thermally conductive layer. Examples of the heating, drying, etc. methods include hot vacuum pressing, hot roller lamination, etc.
[0171] The average thickness of the adhesive layer is preferably 2 μm to 50 μm, more preferably 2 μm to 30 μm, and even more preferably 2 μm to 20 μm. When the average thickness of the adhesive layer is 2 μm or more, there is a tendency to further reduce the gap between the adherend and the thermally conductive sheet, thereby further reducing the contact thermal resistance. When the average thickness of the adhesive layer is 50 μm or less, there is a tendency to improve the thermal conductivity of the thermally conductive sheet.
[0172] The cross section of the heat-conducting layer to be measured can be observed using an electron microscope, and the thickness of three locations can be randomly measured, and the arithmetic average thereof can be used as the average thickness of the adhesive layer. Alternatively, the thickness of three locations of the heat-conducting layer without an adhesive layer and the heat-conducting sheet including an adhesive layer can be randomly measured using a micrometer, and the arithmetic average thereof can be respectively calculated as the average thickness of the heat-conducting layer and the average thickness of the heat-conducting sheet. Then, the average thickness of the adhesive layer can be calculated by subtracting the average thickness of the heat-conducting sheet from the average thickness of the heat-conducting layer.
[0173] When the adhesive layers are formed on the two main surfaces of the heat conductive layer, the average thickness of the adhesive layers refers to the total value of the thicknesses of the adhesive layers formed on the two main surfaces.
[0174] From the viewpoint of further reducing the gap between the adherend and the thermally conductive sheet during bonding, the surface roughness Ra of the thermally conductive sheet (before bonding to the adherend) may be 10 μm or less, and from the viewpoint of the productivity of the thermally conductive sheet, may be 2 μm to 20 μm.
[0175] In the present disclosure, the surface roughness Ra is a value measured based on JIS B0601:2013.
[0176] In the thermally conductive sheet, the thermal conductivity of the thermally conductive layer in the thickness direction is preferably greater than the thermal conductivity of the adhesive layer in the thickness direction. For example, the ratio of the thermal conductivity of the thermally conductive layer in the thickness direction to the thermal conductivity of the adhesive layer in the thickness direction (thermal conductivity of the thermally conductive layer / thermal conductivity of the adhesive layer) may be greater than 1, for example, greater than 1 and less than 20, greater than 1 and less than 10, or 2 to 8.
[0177] The thermal conductivity of the heat conductive layer in the thickness direction and the thermal conductivity of the adhesive layer can be measured by a xenon flash method. When the resin component includes a curable resin component, the thermal conductivity of the adhesive layer refers to the thermal conductivity of the adhesive layer after curing.
[0178] The thermal conductivity of the adhesive layer may be 5.0 W / (m·K) or more, 5.0 W / (m·K) to 20 W / (m·K), or 7.0 W / (m·K) to 15 W / (m·K).
[0179] The thermally conductive sheet may further have a protective film on at least one surface, preferably on both surfaces, so as to protect the pressure-sensitive adhesive surface of the thermally conductive sheet.
[0180] The protective film may be, for example, a resin film of polyethylene, polyester, polypropylene, polyethylene terephthalate, polyimide, polyetherimide, polyether naphthalate, methylpentene, etc., coated paper, coated cloth, and a metal foil of aluminum, etc. These protective films may be used alone or in combination of two or more to form a multilayer film. The protective film is preferably surface treated with a silicone-based, silica-based, or other release agent.
[0181] There is no particular limitation on the use of the thermal conductive sheet. When a semiconductor chip is used as a heating element and a heat sink is used as a heat sink, the thermal conductive sheet disclosed in the present invention is particularly preferably used as a film-like adhesive material for semiconductor chips such as a thermal conductive sheet (TIM1; Thermal Interface Material 1) between the semiconductor chip and the heat sink, a die bonding film, etc. When the thermal conductive sheet is used as a die bonding film, it can be used as a dicing-die bonding integrated film laminated with a dicing tape.
[0182] use Figure 1 Embodiments of the thermally conductive sheet will be described. The thermally conductive sheet of the present disclosure is not limited to the following embodiments.
[0183] Figure 3 The thermally conductive sheet 1A shown includes a thermally conductive layer 11A and adhesive layers 12A and 13A. The adhesive layer 12A is located on one main surface of the thermally conductive layer 11A, and the adhesive layer 13A is located on the other main surface of the thermally conductive layer 11A.
[0184] like Figure 1 As shown, the heat conducting layer 11A in the heat conducting sheet 1A may be uneven because the two main surfaces have concave and convex shapes. Alternatively, the heat conducting layer 11A in the heat conducting sheet 1A may also have two flat main surfaces (for example, see Figure 3 ).
[0185] [Method for manufacturing thermal conductive sheet]
[0186] The method for producing a thermally conductive sheet is not particularly limited as long as it is a method that can obtain a thermally conductive sheet having the above-mentioned structure. The method for producing a thermally conductive sheet comprises: a step of preparing a composition containing the above-mentioned graphite particles (A) (also referred to as a "preparation step"); a step of forming the above-mentioned thermally conductive layer using the above-mentioned composition (also referred to as a "forming step"); and a step of forming an adhesive layer on at least a portion of the main surface of the above-mentioned thermally conductive layer (also referred to as an "adhesive layer forming step").
[0187] <Preparation process>
[0188] In the preparation step, a composition containing graphite particles (A) and any other components (e.g., component (B) that is liquid at 25°C, acrylate polymer (C), hot melt agent (D), antioxidant (E), and other components) is prepared. As a method for mixing the components, any method can be used without particular limitation as long as the components can be uniformly mixed. In addition, the composition can also be prepared by purchasing commercially available substances. For details of the preparation of the composition, reference can be made to paragraph
[0033] of Japanese Patent Publication No. 2008-280496.
[0189] <Formation process>
[0190] In the forming step, the thermally conductive layer is formed using a composition containing graphite particles (A) and any other components. For example, the thermally conductive layer may be formed by molding the composition into a sheet.
[0191] The forming process preferably includes: a process of sheeting the above-mentioned composition to obtain a sheet (also referred to as a "sheet making process"); a process of making a stack of the above-mentioned sheets (also referred to as a "stack making process"); and a process of slicing the side end surface of the above-mentioned stack (also referred to as a "slicing process").
[0192] <<Sheet production process>>
[0193] The sheet making process can be carried out by any method as long as the composition obtained in the previous process can be sheeted, without particular limitation. For example, it is preferably implemented by at least one forming method selected from rolling, pressing, extrusion, and coating. The details of the sheet making process can refer to paragraph
[0034] of Japanese Patent Publication No. 2008-280496.
[0194] 《Laminate production process》
[0195] The laminate production step forms a laminate of the sheets obtained in the previous steps. The laminate can be produced by, for example, sequentially stacking a plurality of independent sheets, folding a single sheet, or rolling a single sheet. For details of the laminate production step, reference can be made to paragraphs
[0035] to
[0037] of Japanese Patent Application Publication No. 2008-280496.
[0196] 《Slicing process》
[0197] The slicing step may be any method as long as the side end surface of the laminate obtained in the previous step can be sliced, and there is no particular limitation. From the viewpoint of forming an extremely effective heat conduction path using the graphite particles (A) that penetrate the thickness direction of the heat conductive layer and further improving the thermal conductivity, it is preferred to slice at a thickness of less than 2 times the mass average particle size of the graphite particles (A). For details of the slicing step, reference can be made to paragraph
[0038] of Japanese Patent Publication No. 2008-280496.
[0198] <Adhesive layer forming process>
[0199] The adhesive layer forming step can be any method as long as it can form an adhesive layer on at least a portion of the main surface of the heat-conducting layer (for example, the sliced sheet obtained by slicing), and there is no particular limitation. For example, a resin composition containing a thermosetting resin component, a heat-conducting filler, a solvent, etc. can be imparted to the main surface of the heat-conducting layer, and the imparted resin composition is heated, dried, etc. to volatilize the solvent. Alternatively, a resin composition can be imparted to a peeling film, and then, after heating and drying, the adhesive layer formed by the heated and dried resin composition is hot-rolled onto the main surface of the heat-conducting layer. As methods of heating, drying, etc., hot vacuum pressing, hot roller lamination, etc. can be listed. The adhesive layer formed on the main surface of the heat-conducting layer can be in a semi-cured state.
[0200] The method for producing a thermally conductive sheet may further include a step of attaching and laminating a protective film on the thermally conductive sheet after the adhesive layer forming step (also referred to as a “lamination step”).
[0201] <Lamination process>
[0202] The lamination step may be performed by any method as long as the thermally conductive sheet obtained in the adhesive layer forming step is attached to the protective film, and is not particularly limited.
[0203] By manufacturing a thermally conductive sheet by this method, an efficient thermal conduction path can be easily formed, and thus there is a tendency that a thermally conductive sheet having high thermal conductivity and excellent adhesion can be obtained.
[0204] 〔Heat dissipation device〕
[0205] The heat dissipation device disclosed in the present invention is a device having a heating element, a heat sink, and the heat conductive sheet disclosed in the present invention disposed between the heating element and the heat sink, wherein the adhesive layer is located on at least a portion of at least one of the main surfaces of the heat conductive layer located on the heating element side and the main surface located on the heat sink side. Preferably, the adhesive layer is located on at least a portion of the main surface of the heat conductive layer located on the heating element side and on at least a portion of the main surface of the heat sink side, respectively. More preferably, the adhesive layer is located on a region of the main surface located on the heating element side facing the heating element and a region of the main surface located on the heat sink side facing the heat sink, respectively.
[0206] Examples of the heat generating body include semiconductor chips, semiconductor packages, power modules, etc. Examples of the heat dissipating body include radiators, heat sinks, water cooling pipes, etc.
[0207] Below, use Figure 2 An example of a heat dissipation device is described in more detail. A heat dissipation device using a semiconductor chip as a heating element and a heat sink as a heat sink is described. A semiconductor chip and a heat sink are examples of a heating element and a heat sink, respectively, and the present disclosure is not limited to them. One surface of a thermal conductive sheet 1 is made to fit tightly with a semiconductor chip 2, and the other surface of the thermal conductive sheet 1 is made to fit tightly with a heat sink 3. The semiconductor chip 2 is fixed to a substrate 4 using an underfill 5, and the heat sink 3 is fixed to the substrate 4 using a sealing material 6, and the fit between the thermal conductive sheet 1 and the semiconductor chip 2 and the heat sink 3 is improved by pressing. In addition, it is not necessary that there is one heating element and one heat sink for each thermal conductive sheet 1. For example, a plurality of semiconductor chips 2 may be provided for a single thermal conductive sheet 1, a single semiconductor chip 2 may be provided for a plurality of thermal conductive sheets 1, or a plurality of semiconductor chips 2 may be provided for a plurality of thermal conductive sheets 1. The adhesive layer is located on the main surface of the thermal conductive sheet 1 on the semiconductor chip 2 side and on the main surface of the thermal conductive sheet 1 on the heat sink 3 side. For example, Figure 3 In the thermally conductive sheet 1 shown, the adhesive layer 13 is located on the main surface of the thermally conductive sheet 1 on the semiconductor chip 2 side, and the adhesive layer 12 is located on the main surface of the thermally conductive sheet 1 on the heat sink 3 side. Furthermore, the adhesive layer 13 may be in contact with the semiconductor chip 2, and the adhesive layer 12 may be in contact with the heat sink 3.
[0208] The heat sink is formed by disposing the heat conductive sheet of the present disclosure between the heating element and the heat sink. By stacking the heating element and the heat sink with the heat conductive sheet interposed therebetween, the heat generated by the heating element can be effectively transferred to the heat sink. By effectively conducting heat, a heat sink can be provided that has a longer service life and functions stably even in long-term use.
[0209] The temperature range in which the thermally conductive sheet can be particularly suitably used may be, for example, -10°C to 150°C, -10°C to 100°C, or -10°C to 80°C. Therefore, as the heat generating element, for example, semiconductor packages, displays, LEDs, electric lights, automotive power modules, and industrial power modules can be cited as preferred examples of heat generating elements.
[0210] Examples of heat sinks include heat sinks using aluminum or copper fins, plates, etc., aluminum or copper blocks connected to heat pipes, aluminum or copper blocks that circulate cooling liquid inside using a pump, and Peltier elements and aluminum or copper blocks having the same.
[0211] The heat sink is formed by bringing the surfaces of the heat conductive sheet into contact with the heating element and the heat sink. There are no particular limitations on the method of bringing the heating element into contact with one surface of the heat conductive sheet and the method of bringing the heat sink into contact with the other surface of the heat conductive sheet as long as they can be fixed in a sufficiently close state.
[0212] For example, the following methods can be cited: placing a heat conductive sheet between a heating element and a heat sink, fixing it with a clamp that can be pressurized to about 0.05MPa to 1Mpa, and heating the heating element in this state, or heating it to about 80°C to 200°C using an oven or the like. In addition, a method using a press that can be heated and pressurized at 80°C to 200°C and 0.05MPa to 1MPa can be cited. The preferred pressure range of this method is 0.10MPa to 1MPa, and the preferred temperature range is 100°C to 180°C. By setting the pressure to more than 0.10MPa or setting the heating temperature to more than 100°C, there is a tendency to obtain excellent adhesion. In addition, by setting the pressure to less than 1MPa or the heating temperature to less than 180°C, there is a tendency to further improve the reliability of the adhesion. It can be considered that this is because the heat conductive sheet can be prevented from being excessively compressed and thus becoming thinner, or the strain or residual stress of the surrounding components can be prevented from becoming too large.
[0213] The heat conductive sheet disposed between the heating element and the heat dissipating element is not particularly limited as long as it is the above-mentioned heat conductive sheet. Figure 1 The heat conductive sheet shown is arranged between the heating element and the heat dissipating element.
[0214] use Figure 1In the case of the thermally conductive sheet 1A shown, by applying heat and pressure while the thermally conductive sheet 1 is disposed between the heat generating element and the heat sink, the adhesive layers 12A and 13A on the main surface of the thermally conductive sheet 1A soften or deform. The gaps generated when the thermally conductive sheet 1A is heated and pressed against the heat generating element and the heat sink are filled with the softened and deformed adhesive layers. This reduces the gaps between the thermally conductive sheet and the heat generating element or the heat sink, and allows the thermally conductive sheet to be closely attached to the adherend with the aid of the adhesive layer. Even when using Figure 1 In the case of the uneven surface of the heat conductive sheet 1A shown in FIG. 1 , the heat conductive sheet 1A may be placed between the heating element and the heat dissipating element and heated and pressed. Thus, the uneven heat conductive sheet 1A is flattened by the pressure, and when manufacturing the heat dissipating device, the heat conductive sheet 1A may be flattened. Figure 3 The flat thermally conductive sheet 1 shown can therefore suppress the generation of gaps between the thermally conductive sheet and the adherend.
[0215] For example, by applying an adhesive layer containing a thermosetting resin component, the adhesive layer deformed by heat and pressure bonding fills the gap between the thermally conductive sheet and the adherend, and the thermosetting resin component is cured by heating. Thus, the thermally conductive sheet and the adherend can be closely attached to each other via the adhesive layer.
[0216] For example, an adhesive layer containing a thermoplastic resin component is applied, and the adhesive layer softened by heat and pressure bonding fills the gap between the thermally conductive sheet and the adherend.
[0217] As a result, the gap between the thermally conductive sheet and the heat generating element or the heat dissipating element is reduced, thereby significantly reducing the contact thermal resistance.
[0218] The ratio (compression rate) of the reduced thickness of the thermally conductive sheet after pressure bonding to the initial thickness before being arranged between the heat generating element and the heat dissipating element and pressure bonded may be 1% to 35%.
[0219] Fixation may be performed using a clamp such as a screw or a spring in addition to a clip, and further fixing by a commonly used means such as an adhesive is preferred from the viewpoint of maintaining close contact.
[0220] At the interface between the heating element and the heat conducting sheet and at the interface between the heat sink and the heat conducting sheet, the porosity calculated as the ratio of the area of the gas region to the area of the measurement region is preferably 0% to 25.0%, and more preferably 0% to 20.0%. As a result, the gaps generated when the heat conducting sheet and the heating element or the heat sink are heated and pressed (for example, the gaps from the unevenness of the heat conducting sheet and the gaps from the unevenness of the heating element or the heat sink) are reduced. As a result, it is inferred that the contact thermal resistance is greatly reduced.
[0221] In the present disclosure, it is preferred that the porosity on both the main surface side of the heat conductive layer where the adhesive layer is present and the main surface side of the heat conductive layer where the adhesive layer is not present satisfy the above numerical range.
[0222] On the main surface side of the heat conductive layer where the adhesive layer is located, the porosity is preferably 0% to 10.0%, more preferably 0% to 5.0%, and even more preferably 0% to 2.0%.
[0223] In the present disclosure, the porosity of the interface can be calculated as follows. First, an ultrasonic imaging diagnostic device (e.g., Insight-300, Insight KK) is used to observe the adhesion state of the interface by reflection method at 35 MHz. The ratio of the area of the gas region without adhesion is calculated, and the porosity of the interface can be calculated based on the following formula.
[0224] Interface porosity (%) = 100 × (area of gas region / area of measurement region)
[0225] The numerical range of the void ratio at the interface can be adjusted by, for example, adjusting the thickness of the adhesive layer, the composition of the resin composition forming the adhesive layer, the compression rate of the thermally conductive sheet, and the like.
[0226] [Example]
[0227] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples.
[0228] (Example 1 to Example 2)
[0229] The following materials were charged into a kneader (MORIYA MA CORPORATION, DS3-SGHM-E type pressurized double-arm kneader) at the mixing ratio (volume %) shown in Table 1, and kneaded at a temperature of 150° C. to obtain a composition.
[0230] <Graphite particles (A)>
[0231] (A)-1: scaly expanded graphite particles (Showa Denko Materials Co., Ltd. "HGF-L", mass average particle size: 270 μm, confirmed by the aforementioned method using X-ray diffraction measurement that the six-membered ring planes in the crystal are oriented along the plane direction of the scaly particles).
[0232] <Liquid component (B)>
[0233] (B)- 1 :Isobutylene-n-butene copolymer (NOF Corporation "NOF Polybutene TM EMAWET (registered trademark), grade 30N)
[0234] (B)- 2 : Homopolymer of isobutylene (Nippon Oil Corporation "Tetrax 6T")
[0235] <Acrylate polymer (C)>
[0236] (C)-1: Acrylate copolymer resin (butyl acrylate / ethyl acrylate / acrylonitrile / acrylic acid copolymer, weight average molecular weight: 530,000, Tg = -39°C)
[0237] <Hot melt (D)>
[0238] (D)-1: Hydrogenated petroleum resin (Arakawa Chemical Industries, Ltd. "Arkon P90")
[0239] <Antioxidant (E)>
[0240] (E)-1: Hindered phenol antioxidant (ADK STAB AO-60 from ADEKA Corporation)
[0241] (Fabrication of thermal conductive layer)
[0242] The kneaded composition was placed in an extrusion molding machine (Parker Co., Ltd., trade name: HKS 40-15 extruder), extruded into a flat plate shape with a width of 20 cm and a thickness of 1.5 mm to 1.6 mm to obtain a primary sheet. The primary sheet obtained was pressed and punched with a 40 mm × 150 mm die blade, 61 punched sheets were stacked, and a spacer with a height of 80 mm was clamped in a manner of 80 mm. Pressure was applied to the stacking direction at 90°C for 30 minutes to obtain a 40 mm × 150 mm × 80 mm laminate. Next, the 80 mm × 150 mm side end surface of the laminate was sliced with a woodworking slicer to obtain a thermal conductive layer with a thickness of 0.11 mm.
[0243] (Manufacturing of thermal conductive sheet)
[0244] (Example 1)
[0245] A resin composition containing 6 parts by mass of a thermosetting resin component (bisphenol F epoxy resin), 4 parts by mass of a cresol novolac epoxy resin), 8 parts by mass of a phenolic resin, 6 parts by mass of an acrylic resin, 76 parts by mass of a thermally conductive filler (silver particles, particle size 1.5 μm), and 39 parts by mass of a solvent (cyclohexanone) was prepared. The prepared resin composition was applied to a release film and dried in an oven at 130° C. A heat roller laminate was performed at 70° C. on one main surface of the thermally conductive layer obtained as described above to obtain a thermally conductive sheet having an adhesive layer (adhesive layer 1 in Table 2) formed on one main surface.
[0246] (Example 2)
[0247] A resin composition containing 4 parts by mass of a thermosetting resin component (bisphenol F epoxy resin), 3 parts by mass of a cresol novolac epoxy resin), 6 parts by mass of a phenolic resin, 5 parts by mass of an acrylate resin, 83 parts by mass of a thermally conductive filler (silver particles, particle size 1.5 μm), and 39 parts by mass of a solvent (cyclohexanone) was prepared. The prepared resin composition was applied to a release film and dried in an oven at 130° C. A heat roller laminate was performed at 70° C. on one main surface of the thermally conductive layer obtained as described above to obtain a thermally conductive sheet having an adhesive layer (adhesive layer 2 in Table 2) formed on one main surface.
[0248] (Comparative Example 1)
[0249] The materials shown in Table 1 were mixed, laminated, pressed, and sliced in the same steps as Examples 1 and 2 at the mixing ratios (volume %) shown in Table 1 to produce a thermally conductive layer. In each comparative example, no adhesive layer was formed, and the thermally conductive layer was used as a thermally conductive sheet.
[0250] Table 1
[0251]
[0252] The thermally conductive sheets of Examples 1 to 2 and Comparative Example 1 were evaluated by the following methods. The results are shown in Tables 2 and Figure 4 .
[0253] (Determination of thermal resistance)
[0254] Thermal resistance was measured using a desktop xenon flash analyzer (LFA467Hyper Flash). A Φ14 mm thermally conductive sheet was sandwiched between 1 mm copper plates to produce a three-layer structure sample. As sample preparation conditions, pressurization was performed at a temperature of 150°C and a pressure of 0.14 MPa for 3 minutes. In the case of a thermosetting resin, in order to cure the resin, it was heated in an oven at 175°C for 1 hour and fully cooled at room temperature. In addition, as a pretreatment for the measurement, the copper surface was blackened with carbon spray, and then the measurement was performed. The thermal conductivity λ after removing the influence of the copper plate portion from the three-layer structure was obtained, and based on the obtained thermal conductivity λ and thickness t, the thermal conductivity per unit area (1 cm) was calculated as follows according to the following formula. 2 ) thermal resistance value X(K·cm 2 / W).
[0255] X=(10×t) / λ
[0256] t: Thickness of the thermally conductive sheet of Examples 1 to 4 or Comparative Example 1 (mm)
[0257] λ: Thermal conductivity (W / (m·K))
[0258] (Evaluation of interface porosity)
[0259] For the sample of the three-layer structure prepared according to the method described in (Determination of thermal resistance), the porosity of the interface was evaluated as follows. Using an ultrasonic imaging diagnostic device (Insight-300, Insight KK), the adhesion state of the interface was observed by the reflection method at 35 MHz, a gain level of 10 dB, and a contrast threshold of 30% to 70%. Furthermore, the image was binarized using image analysis software (ImageJ) (specifically, the histogram of 0 to 83 was used as the black part and 84 to 255 was used as the white part for black and white conversion), and the area of Φ11 mm (the area of the measurement area, it should be noted that) was calculated. Figure 4 The ratio of the area of the gas region not attached in the Φ14 mm image is shown in the figure, and the porosity (%) of the interface is calculated based on the following formula.
[0260] Interface porosity (%) = 100 × (area of gas region / area of measurement region)
[0261] (Thickness Evaluation)
[0262] The thickness of the adhesive layer before hot roll lamination was measured using a micrometer in Examples 1 and 2. Next, the thermally conductive sheets of Examples 1 and 2 and Comparative Example 1 were compressed under the same conditions. The maximum thickness of the thermally conductive sheet after compression ("thickness after compression" in Table 2) was then measured using a micrometer.
[0263] Table 2
[0264]
[0265] It was confirmed that Examples 1 and 2 using a resin composition containing a resin component and a thermally conductive filler and forming an adhesive layer on the main surface of the thermally conductive layer can reduce thermal resistance compared to Comparative Example 1 in which no adhesive layer is formed on the main surface of the thermally conductive layer.
[0266] (Fabrication of Heat Conductive Layer 1)
[0267] The materials shown in Table 1 were mixed, laminated, pressed, and sliced according to the mixing ratios (volume %) in Table 1 by the same steps as in Examples 1 and 2 to produce the thermal conductive layer 1 .
[0268] (Fabrication of Heat Conductive Layer 2)
[0269] With respect to the formulation in Table 1, a thermally conductive layer 2 was prepared in the same manner as the thermally conductive layer 1 except that the blending ratio of the graphite particles (A) was increased to 40.0% by volume and the blending ratios of the other components were changed to those shown in Table 3.
[0270] Table 3
[0271]
[0272] (Manufacturing of thermal conductive sheet)
[0273] (Example 3)
[0274] A resin composition containing 16 parts by mass of bisphenol A epoxy resin, 1 part by mass of bisphenol S, 83 parts by mass of a thermally conductive filler (silver particles, particle size 1.5 μm), 0.1 parts by mass of triphenylphosphine, and 32 parts by mass of a solvent (methyl ethyl ketone) as shown below was prepared. The prepared resin composition was applied to a release film, heated at 70°C for 5 minutes, and then heated at 160°C for 2 hours to react the bisphenol A epoxy resin and bisphenol S to form a thermoplastic epoxy resin. A heat roller laminate was performed at 140°C on one main surface of the thermally conductive layer 1 obtained as described above to obtain a thermally conductive sheet having an adhesive layer (adhesive layer 3 in Table 4) formed on one main surface.
[0275] The thickness of the adhesive layer before hot roll lamination measured with a micrometer was 10 μm.
[0276] The pressure when preparing a three-layer structure sample for the thermal resistance measurement described later was set to 0.14 MPa.
[0277] (Example 4)
[0278] In the same manner as in Example 3, a thermally conductive sheet having an adhesive layer (adhesive layer 3 in Table 4) formed on one main surface was obtained.
[0279] The thermal resistance was measured in the same manner as in Example 3 except that the pressure condition when preparing the three-layer structure sample for the thermal resistance measurement was changed to 0.28 MPa.
[0280] (Example 5)
[0281] A thermally conductive sheet having adhesive layers (adhesive layer 3 in Table 4) formed on both main surfaces was obtained in the same manner as in Example 3 except that heat roll lamination was performed on both main surfaces of the thermally conductive layer 1 obtained as described above.
[0282] The pressure when preparing a three-layer structure sample for the thermal resistance measurement described later was set to 0.14 MPa.
[0283] (Example 6)
[0284] In the same manner as in Example 5, a thermally conductive sheet having adhesive layers (adhesive layer 3 in Table 4) formed on the two main surfaces was obtained.
[0285] The thermal resistance was measured in the same manner as in Example 5 except that the pressure condition when preparing the three-layer structure sample for the thermal resistance measurement was changed to 0.28 MPa.
[0286] (Example 7)
[0287] A thermally conductive sheet having adhesive layers (adhesive layers 3 in Table 4) formed on two main surfaces was obtained in the same manner as in Example 6 except that the thermally conductive layer 1 was changed to the thermally conductive layer 2.
[0288] The pressure when preparing a three-layer structure sample for the thermal resistance measurement described later was set to 0.28 MPa.
[0289] (Comparative Examples 2 and 3)
[0290] In Comparative Examples 2 and 3, no adhesive layer was formed, and the thermally conductive layer 1 was used as a thermally conductive sheet.
[0291] The pressures when preparing a three-layer structure sample for thermal resistance measurement described later were set to 0.14 MPa and 0.28 MPa, respectively.
[0292] (Comparative Example 4)
[0293] In Comparative Examples 2 and 3, no adhesive layer was formed, and the thermally conductive layer 2 was used as a thermally conductive sheet.
[0294] The pressure when preparing a three-layer structure sample for the thermal resistance measurement described later was set to 0.28 MPa.
[0295] In the thermally conductive sheets of Examples 3 to 7 and Comparative Examples 2 to 4, the thickness of the thermally conductive sheets after compression was determined in the same manner as described above, and the thermal resistance of the thermally conductive sheets was determined as follows.
[0296] (Determination of thermal resistance)
[0297] Thermal resistance was measured using a desktop xenon flash analyzer (LFA 447Hyper Flash). A 15 mm square thermally conductive sheet was sandwiched between 1 mm copper plates to prepare a three-layer structure sample. As sample preparation conditions, the temperature was 150°C and the pressure was 0.14 MPa or 0.28 MPa. In order to fully adhere the resin to the copper plate, they were heated in an oven at 150°C for 30 minutes, then heated in an oven at 180°C for 1 hour, and fully cooled at room temperature. In addition, as a pretreatment for the measurement, the copper surface was blackened with carbon spray, and then the measurement was performed. The thermal conductivity λ after removing the influence of the copper plate part from the three-layer structure was obtained, and based on the obtained thermal conductivity λ and thickness t, the thermal conductivity per unit area (1cm 2 ) thermal resistance value X(K·cm 2 / W).
[0298] X=(10×t) / λ
[0299] T: Thickness of the thermally conductive sheet of Examples 1 to 4 or Comparative Example 1 (mm)
[0300] λ: Thermal conductivity (W / (m·K))
[0301] Table 4
[0302]
[0303] The thermal conductivity of the heat conducting layer / thermal conductivity of the adhesive layer in Examples 3 to 7 was determined in the same manner as in Examples 1 and 2. Furthermore, the porosity of the interface was determined as follows. The results are shown in Tables 5 and Figure 5 .
[0304] In addition, when the adhesive layer is arranged on both surfaces of the thermal conductive layer, the porosity of the interface (the surface with the adhesive layer) is the arithmetic mean of the porosities of the two surfaces.
[0305] When no adhesive layer is disposed on both surfaces of the heat conductive layer, the porosity of the interface (the surface without the adhesive layer) is the arithmetic mean of the porosities of the two surfaces.
[0306] (Evaluation of interface porosity)
[0307] For the sample of the three-layer structure prepared according to the method described in (Determination of thermal resistance), the porosity of the interface was evaluated as follows. Using an ultrasonic imaging diagnostic device (Insight-350, Insight KK), the adhesion state of the interface was observed by reflection method at 75 MHz, a gain level of 10 dB, and a contrast threshold of 30% to 70%. Furthermore, the image was binarized by image analysis software (ImageJ) (specifically, 0 to 216 of the histogram was used as the black part and 217 to 255 as the white part for black and white), and the ratio of the area of the gas area without adhesion in the area of 10.4 mm square (the area of the measurement area) was calculated, and the porosity (%) of the interface was calculated based on the following formula.
[0308] Interface porosity (%) = 100 × (area of gas region / area of measurement region)
[0309] Table 5
[0310]
[0311] As shown in Table 4, it was confirmed that in Examples 3 to 7 in which a resin composition containing a thermoplastic resin component and a thermally conductive filler was used and an adhesive layer was formed on the main surface of the thermally conductive layer, thermal resistance could be reduced compared with Comparative Examples 2 to 4 in which the adhesive layer was not formed on the main surface of the thermally conductive layer.
[0312] As shown in Table 5, the values of the interface porosity of Examples 3 to 7 are lower than those of Comparative Examples 2 to 4, and it is presumed that the thermal resistance can be reduced by reducing the interface porosity.
[0313] All documents, patent applications, and technical standards described in this specification are incorporated by reference into this specification to the same extent as if each individual document, patent application, and technical standard was specifically and individually described as being incorporated by reference.
Claims
1. A thermally conductive sheet comprising: a heat conductive layer, the heat conductive layer comprising at least one graphite particle (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, wherein in the case of the flaky particles, the surface direction is oriented along the thickness direction of the heat conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the heat conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the heat conductive layer; and The adhesive layer comprises a resin component and a thermally conductive filler, and the adhesive layer is located on at least a portion of the main surface of the thermally conductive layer.
2. The thermally conductive sheet according to claim 1, wherein: The resin component includes at least one selected from the group consisting of a curable resin component, a pressure-sensitive adhesive resin component, and a thermoplastic resin component.
3. The thermally conductive sheet according to claim 2, wherein: The resin component is a curable resin component, and the adhesive layer is in a semi-cured state.
4. The thermally conductive sheet according to any one of claims 1 to 3, wherein The resin component includes a thermoplastic resin component.
5. The thermally conductive sheet according to any one of claims 1 to 4, wherein The thermoplastic resin component includes a thermoplastic epoxy resin.
6. The thermally conductive sheet according to any one of claims 1 to 5, wherein The thermally conductive filler is at least one particle selected from the group consisting of silver, copper, aluminum, aluminum oxide, aluminum hydroxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, silicon carbide, silicon dioxide, aluminum fluoride, calcium fluoride, and zinc oxide.
7. The thermally conductive sheet according to claim 6, wherein: The thermally conductive filler is silver particles.
8. The thermally conductive sheet according to any one of claims 1 to 7, wherein The content of the thermally conductive filler is 70% by mass to 99% by mass based on the total amount of the adhesive layer.
9. The thermally conductive sheet according to any one of claims 1 to 8, wherein The average thickness of the adhesive layer is 2 μm to 50 μm.
10. A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet according to any one of claims 1 to 9 disposed between the heating element and the heat dissipation element, in, The adhesive layer is located on at least a portion of at least one of a main surface of the heat conductive layer located on the heating element side and a main surface of the heat conductive layer located on the heat radiating element side.
11. A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet according to any one of claims 1 to 9 disposed between the heating element and the heat dissipation element, in, At least one of the interface between the heating element and the heat conductive sheet and the interface between the heat dissipating element and the heat conductive sheet, a porosity calculated as a ratio of an area of a gas region to an area of a measurement region is 0% to 25%.
12. A method for producing a thermally conductive sheet, the method comprising producing the thermally conductive sheet according to any one of claims 1 to 9, The manufacturing method of the thermal conductive sheet comprises: A step of preparing a composition containing the graphite particles (A); A process of forming the thermal conductive layer using the composition; and The step of forming an adhesive layer on at least a portion of the main surface of the heat conductive layer.
Citation Information
Patent Citations
Heat conductive material and manufacturing method thereof
JP2001250894A
Heat conducting sheet and its manufacturing method
JP2002026202A
Heat-conductive sheet, method for producing the same, and heat radiator using the same
JP2008280496A